Synthesis, Spectral Characterization and Antimicrobial Activity of Substituted Thiazolyl Derivatives of 2-Quinolones - Katagi, M. S.; Bolakatti, G. S.; Badiger, A. M.; Satyanarayana, D.; Mamledesai, S. N.; Sujatha, M. L. (Drug Research, 2013)
A series of new 3-(2-substituted amino/substituted hydrazino-1,3-thiazol-4-yl)-4-hydroxy-1-methyl/phenylquinolin-2 (1H)-one hydroiodide 3a–3f and 4a–4f derivatives were prepared by heating 3-Acetyl-4-hydroxy-1-methyl/phenyl quinolin-2 (1H)-one 2a–2b with substituted thiourea and substituted thiosemicarbazide in presence of iodine in n-butanol. The title compounds were characterized on the basis of IR, 1H NMR, 13C NMR and Mass spectral (MS) studies. Further title compounds were evaluated for antibacterial and antifungal by Agar diffusion assay method where as antitubercular activity by Micro-plate Alamar Blue Assay (MABA). Among 12 synthesized novel compounds 3a, 3b, 4d exhibited promising antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa.3a, 3b, 3e, 4d, 4e showed good antifungal activity against Candida albicans and Aspergillus niger.3a, 3d, 4d showed good antitubercular activity against Mycobacterium tuberculosis H37Rv strain.
Keywords: 2-quinolone; aminothiazole; antibacterial; antifungal; antitubercular